Dystocia due to hydrocephalus fetus in Murrah buffalo and its obstetrical management - Kumar, Sandeep; Pandey, Anand Kumar; Pradeep,; Saini, Gitesh; Singh, Gyan (The Indian Journal of Animal Reproduction, 2022)
A hydrocephalic calf was delivered per-vaginum after drainage of excessive cerebrospinal fluid (CSF) fluid by giving a stab incision at the cranium of the fetus in a Murrah buffalo. The dam recovered uneventfully.
Keywords: Buffalo; Cranium; Dystocia; Hydrocephalus